Communication media and the “8,000 Trial” - Acevedo Moreno, Elvia Elena (Folios, revista de la Facultad de Comunicaciones y Filología, 2016)
This text presents some of the most highlighted features of the coverage that the newspapers El Tiempo, El Espectador and the magazine Semana have did about the ”8,000 Trial” during three specific periods. This text is inscribed in the analysis of content line and the conclusion are retaken from a Phd research defended at the University of Sao Paulo. The 8,000 trial is the generic name given from the media to judicial investigations about the drug trafficking income to 1994 presidential election campaign, which Ernesto Samper Pizano has emerged victorious. The text is constantly interweaved with the reflections that, at that time, the analysts did about the political crisis provoked by the 8,000 trial, and with the role in general of the press. Profusely information about this episode led to the great success and the big mistake of the media: they allowed that the country knows that happened, and, at same time, the contributed to the attention began to focus more in revolves around relevant affairs, and less in revolves around the true causes were at the base of the crisis.